Estudio técnico y ecòmico para la creación de un centro de control y vigilancia de la fauna doméstica y silvestre del Gad Municipal de Quevedo, año 2015 - Vera Galarza, Lidia Edith (2015)
This research was conducted in order to participate actively in concrete actions to raise awareness about the reality of the Urban Wildlife in Canton Quevedo, within the legal framework, such as social, this project proposes to highlight the importance of putting into operation a center that is responsible for the control and monitoring of urban wildlife, and encourage responsible pet ownership and the humane treatment of them. Animal welfare and public health is an issue for all cities who no longer know what to do with so many animals; source of spread of disease vectors that serve the same and environmental pollution…..